EVALUASI DAN PERBAIKAN DESAIN UI/UX DENGAN METODE USER CENTERED DESIGN PADA WEBSITE SMK NEGERI 1 BINANGUN - Rahayu, Ratna Budi Sri; Prasetyo, Novian Adi; Wijayanto, Aditya (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
The SMKN 1 Binangun website is a website-based software system that is used to convey the latest information or news from the school to students. This website began to be used in 2020, but in its use there were several problems experienced by users. These obstacles include an interface that is not good in terms of design, page layout and website content, apart from that in terms of website appearance which is less attractive and less attractive to users and lack of updates. Incomplete information can be added with information on expertise programs and infrastructure, there is no search menu, many menus are still empty and not functioning, the alumni data update flow on the alumni menu is still confusing and can be accessed by non-alumni and website visitor traffic is still low. Based on these problems, it is necessary to evaluate and improve the UI/UX design to produce a website that fits user needs. The results of this study are improvements to the user interface of the SMKN 1 Binangun website from the user side (front-end). The results of usability testing using UEQ obtained a comparisson to benchmark rating between above average to good, indicating that the website design improvement was better than the previous design, this was reinforced by hypothesis analysis which stated that the H0 hypothesis was rejected and H1 was accepted according to the UEQ average value.